Cascading effects of freshwater salinization on plankton communities in the Sierra Nevada. Issue 1 (5th December 2020) - Moffett, Emma R.; Baker, Henry K.; Bonadonna, Christine C.; Shurin, Jonathan B.; Symons, Celia C.
Abstract: Runoff containing road salt (sodium chloride, NaCl) causes the salinization of inland freshwaters, with potentially severe impacts on aquatic species. We performed a mesocosm experiment to test the effects of salinization on plankton community structure in an oligotrophic mountain lake with a limited history of elevated salt concentrations. We exposed plankton communities to a gradient of 30 salt concentrations ranging from 1 to 2900 Cl −  mg L −1 for 6 weeks. Adding salt increased zooplankton biomass at concentrations < 500 mg Cl −  L −1 while reducing phytoplankton biomass. Zooplankton biomass declined precipitously at higher concentrations, with phytoplankton biomass showing a mirror image increase. The initial increase in zooplankton biomass with salt addition suggests that zooplankton are salt‐limited at low ionic concentrations. Additionally, the inverse response of zooplankton and phytoplankton suggests that salinity mainly affects phytoplankton biomass via changes in top‐down regulation by grazers.